Carta de Roberto H. Todd a Francisco Rivera Collazo - Todd, Roberto H.; Rivera Collazo, Francisco (My University, 1936)
Solicitud de la hija de Martínez Dávila a Roberto H. Todd.
Keywords: Martínez Dávila, Manuel A.,1883-1934